2014
DOI: 10.4209/aaqr.2013.09.0303
|View full text |Cite
|
Sign up to set email alerts
|

Study and Application of a Cyclone for Removing Amine Droplets from Recycled Hydrogen in a Hydrogenation Unit

Abstract: Recycled hydrogen is fed into a hydrogenation unit using a compressor with oil gas, amine droplets, and other hazardous gases at a super-high operating pressure after having been passed through a desulfurization system. This study developed a gas-liquid cyclone for removing amine droplets in recycled hydrogen based on computational fluid dynamics (CFD), an experimental study and industrial application. The results showed that the highest separation efficiency of the gas-liquid cyclone was 94.8% (experiment) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 31 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The main design parameters of the central exhaust pipe consisted of the insertion depth (S) and pipe diameter (D x ). Previous studies have revealed D x /D 1 = 0.25-0.5 as a suitable range for the central exhaust pipe (Ma et al, 2014;, and the present study adopted 0.45 for the D x /D 1 ratio (i.e., D x = 45mm). In addition, the present study adopted 0.7 for the S/H ratio (i.e., S = 630 mm) suggested in Bogodage et al (2016) and Safikhani and Mehrabian (2016).…”
Section: Gas Cyclone-liquid Jet Absorption Separatormentioning
confidence: 98%
“…The main design parameters of the central exhaust pipe consisted of the insertion depth (S) and pipe diameter (D x ). Previous studies have revealed D x /D 1 = 0.25-0.5 as a suitable range for the central exhaust pipe (Ma et al, 2014;, and the present study adopted 0.45 for the D x /D 1 ratio (i.e., D x = 45mm). In addition, the present study adopted 0.7 for the S/H ratio (i.e., S = 630 mm) suggested in Bogodage et al (2016) and Safikhani and Mehrabian (2016).…”
Section: Gas Cyclone-liquid Jet Absorption Separatormentioning
confidence: 98%